2015
DOI: 10.3758/s13414-015-0906-5
|View full text |Cite
|
Sign up to set email alerts
|

Color perception is impaired in baseball batters while performing an interceptive action

Abstract: In order to test the theoretical idea that experts rely more on the dorsal stream than the ventral stream during interceptive action for the interception of a moving target, the present study investigates the perception of color (dominant in ventral processing) during interceptive action in fast-ball sports. Twelve college baseball players and 12 non-baseball players performed a coincident-timing task with target color changes (from white to red, blue, or white) at various time points (at 100, 200, or 300 ms b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…After attempting to hit the two pitches, participants were asked to verbally report which ball speed they perceived to be faster (i.e., that in the “first” or “second” pitch). Although there has been some criticism of the use of unnatural response modes, including verbal responses, for testing perceptual expertise in interceptive sport ( 43 45 ), we used the verbal response because Takamido et al had already shown that the pitching movement speed influences performance in the ball-speed evaluation task irrespective of whether the participant's response is recorded verbally ( 24 ) or through movement ( 46 ). The reference stimulus always showed the participant-specific natural pitching-movement-speed.…”
Section: Methodsmentioning
confidence: 99%
“…After attempting to hit the two pitches, participants were asked to verbally report which ball speed they perceived to be faster (i.e., that in the “first” or “second” pitch). Although there has been some criticism of the use of unnatural response modes, including verbal responses, for testing perceptual expertise in interceptive sport ( 43 45 ), we used the verbal response because Takamido et al had already shown that the pitching movement speed influences performance in the ball-speed evaluation task irrespective of whether the participant's response is recorded verbally ( 24 ) or through movement ( 46 ). The reference stimulus always showed the participant-specific natural pitching-movement-speed.…”
Section: Methodsmentioning
confidence: 99%
“…It is also possible that the sensory processing measurement used in this study (reaction time to a yellow light appearing on a computer screen, flashing light in a sensory sensitivity test) primarily activated processing in the ventral visual stream, which is responsible for processing visual information such as object recognition and color perception ( Ungerleider & Mishkin, 1982 ), while the environment of the volleyball players mainly requires the use of the dorsal visual stream, which processes more coarse visual information such as motion, depth and spatial location. The results indicate that athletes required to quickly respond to moving stimuli rely more on their dorsal stream ( Sasada et al, 2015 ). However, research suggests that there is an interaction between the dorsal and ventral pathways in action contexts ( van Polanen & Davare, 2015 ), so stroboscopic excitation of the dorsal pathway may influence the ventral pathway.…”
Section: Discussionmentioning
confidence: 97%
“…The target changed color during its trajectory, and participants were asked to identify the final color. Sasada et al 22 found that the color perception of the baseball players was worse in the coupled response than in the uncoupled one, a difference not observed in the non-baseball players. These results were interpreted to suggest that the experts relied more on the dorsal stream during actual interceptive actions than novices did.…”
Section: Wwwoptvisscicommentioning
confidence: 96%
“…In an elegant test of the two-visual-system hypothesis, Sasada and colleagues 22 tested whether the dorsal stream is more likely to be engaged in skilled baseball batters when hitting a ball rather than when perceiving its position. Because color perception is processed largely in the ventral but not dorsal stream, Sasada et al 22 hypothesized that color perception should be impaired when the dorsal stream is engaged (i.e., when an action is produced).…”
Section: How Has the Two-visual-system Hypothesis Been Interpreted In...mentioning
confidence: 99%
See 1 more Smart Citation